SYNTHESIS AND CHARACTERIZATION OF COBALT (III) COMPLEX OF SALICYLALDEHYDE BENZOYL HYDRAZONE - Shrestha, Sabita (Journal of Institute of Science and Technology, 2017)
Cobalt Complex of type [Co(Hsbh)2(NO3)(H2O)]. 3H2O was synthesized and characterized by different analytical procedures, molar conductance, infrared and electronic spectral studies. The complex was found to be 1:2 metal ligand ratio. Molar conductance measurement shows non electrolyte nature of complex. Dehydration studies indicate the presence of coordinated as well as lattice water molecules. Infrared spectral studies indicate that ligand undergo keto enol tautomerism and bond to the metal ion via enolic oxygen and NH2 group. The electronic spectrum shows octahedral geometry around central cobalt (III) atom. Journal of Institute of Science and Technology Volume 22, Issue 1, July 2017, page: 132-136